2007
DOI: 10.2337/dc07-0119
|View full text |Cite
|
Sign up to set email alerts
|

Normal Glucose Tolerance and Gestational Diabetes Mellitus

Abstract: OBJECTIVE -The aim of this article was to define the metabolic phenotype of pregnant women with one abnormal value (OAV) during an oral glucose tolerance test (OGTT) and to test whether OAV could be considered metabolically comparable to gestational diabetes mellitus (GDM) or a specific entity between GDM and normal pregnancy. RESEARCH DESIGN AND METHODS-After 100-g 3-h OGTTs, 4,053 pregnant women were classified as having GDM, OAV, or normal glucose tolerance (NGT). Those with OAV were subdivided into three s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
1
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 31 publications
6
42
1
4
Order By: Relevance
“…Indeed, high IR is considered a leading risk factor for GDM (19). Our results were in accordance with those of previous studies (20,21) on average HOMA-IS and HOMA-IR values of IGT, indicating that IGT represents an intermediate phenotype between NGT and GDM.…”
Section: B a B Asupporting
confidence: 93%
“…Indeed, high IR is considered a leading risk factor for GDM (19). Our results were in accordance with those of previous studies (20,21) on average HOMA-IS and HOMA-IR values of IGT, indicating that IGT represents an intermediate phenotype between NGT and GDM.…”
Section: B a B Asupporting
confidence: 93%
“…Traditionally, it has been felt that GIGT represents an intermediate phenotype between normal glucose tolerance (NGT) and GDM (6,7). Interestingly, however, it has recently emerged that GIGT is actually a heterogeneous metabolic disorder, as defined by the glycemic response on the OGTT (8).…”
Section: G Estational Diabetes Mellitus (Gdm)mentioning
confidence: 99%
“…They showed that the insulinogenic index was significantly lower in the traditional GDM group (two or more abnormal values on OGTT) compared with the normal OGTT group [20]. Di Cianni et al reported that pregnant women with OAV and the traditional GDM group were older and had higher BMIs than the group with normal glucose tolerance [21]. Therefore, pregnant women with normal glucose tolerance had the highest ISI-composite.…”
Section: Discussionmentioning
confidence: 99%
“…Early-phase insulin secretion was found to be significantly reduced in pregnant women with OAV and the traditional GDM group, compared with pregnant women having normal glucose tolerance. They concluded that pregnant women with OAV and pregnant women with traditional GDM are clinically indistinguishable, and both groups are different from women with normal glucose tolerance [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation